agriwater: An R package for spatial modelling of energy balance and actual evapotranspiration using satellite images and agrometeorological data - Ferreira Silva, Cesar de Oliveira [UNESP]; Castro Teixeira, Antonio Heriberto de; Manzione, Rodrigo Lilla [UNESP] (Elsevier B.V., 2019)
Aiming to subsidize the rational water resources management, an R package called agriwater was created in order to obtain the energy balance on the soil and actual evapotranspiration using satellite imagery and agrometeorological data. This package apply the Simple Algorithm for Evapotranspiration Retrieving - SAFER to calculate the evapotranspiration fraction ETr (or ETA ET0-1), actual evapotranspiration (ETA) and latent heat flux (lambda E); the Slob equation calculate the net radiation (R-N); ground heat flux (G) is modeled from R-N; and the sensible heat flux (H) is retrieved as the residue of the energy balance equation. Landsat-8 (with and without thermal bands), Sentinel-2 and MODIS digital images can be used. Results are presented in raster format and can be post-processed by GIS analysis or anothers R procedures. A study case using Sentinel-2 images and agrometeorological data of a semiarid area from Brazil was performed. The requirements and conditions for use of the package are explained.
Keywords: Actual evapotranspiration; Evapotranspiration fraction; Net radiation; Latent heat flux; Sensible heat flux; Soil heat flux